2014
DOI: 10.1371/journal.pone.0105918
|View full text |Cite
|
Sign up to set email alerts
|

Might Depression, Psychosocial Adversity, and Limited Social Assets Explain Vulnerability to and Resistance against Violent Radicalisation?

Abstract: BackgroundThis study tests whether depression, psychosocial adversity, and limited social assets offer protection or suggest vulnerability to the process of radicalisation.MethodsA population sample of 608 men and women of Pakistani or Bangladeshi origin, of Muslim heritage, and aged 18–45 were recruited by quota sampling. Radicalisation was measured by 16 questions asking about sympathies for violent protest and terrorism. Cluster analysis of the 16 items generated three groups: most sympathetic (or most vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 45 publications
2
73
2
6
Order By: Relevance
“…Much has been made of Anders Breivik that fits well with this kind of understanding (see inter alia Billig and Stalne 2012). In a similar vein, Bhui et al (2014) report a link between mild depression, expressed support for violence and tendencies towards radicalisation/violent extremism. The extent to which this kind of approach fits with the available evidence pertaining to violent extremism motivated by religion is moot since suicide attacks prevent subsequent psychological analysis.…”
Section: Thinking About Violent Extremismmentioning
confidence: 86%
“…Much has been made of Anders Breivik that fits well with this kind of understanding (see inter alia Billig and Stalne 2012). In a similar vein, Bhui et al (2014) report a link between mild depression, expressed support for violence and tendencies towards radicalisation/violent extremism. The extent to which this kind of approach fits with the available evidence pertaining to violent extremism motivated by religion is moot since suicide attacks prevent subsequent psychological analysis.…”
Section: Thinking About Violent Extremismmentioning
confidence: 86%
“…Gruenewald et al (2013) have pointed to the significance of mental instability/illness, military background, age, and relationship status as distinguishing 'loners' from other kinds of extremists: a product of what they call 'self-radicalisation'. In a similar vein, Bhui et al (2014) report a link between mild depression and expressed support for violence and tendencies towards radicalisation. However, as Pape (2006) argues, it is important to remember that the vast majority of suicide bombers also belong to, or are affiliated with, organizations making the attribution of psychological factors alone difficult.…”
Section: Three French Men: Criminology and Violent Extremismmentioning
confidence: 86%
“…54 Bhui et al see a spiral at play here. 55 Their groundbreaking study into depression and sympathy for violent protest and terrorism showed a direct correlation between weakened social cohesion, depression, and support for extreme views. It also identified a self-perpetuating pattern, with increased violence and terrorist acts leading to increased breakdown of social capital, depression, and higher sympathy for extreme acts.…”
Section: Known Lone Wolf Terrorist Attacks In 2016mentioning
confidence: 99%